Determination of volatile 'restricted substances' in flavourings and their volatile raw materials by GC‐MS. (10th December 2014) - Cachet, T.; Brevard, H.; Cantergiani, E.; Chaintreau, A.; Demyttenaere, J.; French, L.; Gassenmeier, K.; Joulain, D.; Koenig, T.; Leijs, H.; Liddle, P.; Loesing, G.; et al.
Abstract Many flavour regulations around the world contain a list of so‐called 'restricted substances' (RS), i.e. substances that occur naturally in source materials for flavourings and food ingredients with flavouring properties, but whose presence in certain foods is restricted and/or for which maximum levels are set, for example, the European regulation 1334/2008. Only a few publications refer to the determination of RS in compound flavourings or their raw materials, and the latter only concern the analysis of one or two individual RS in single essential oils. The Working Group on Methods of Analysis of the International Organization of the Flavor Industry (IOFI) has developed a method for the rapid routine determination of β‐asarone, coumarin, menthofuran, methylchavicol, methyleugenol, pulegone, safrole and α‐ and β‐thujones in flavourings and their raw materials by gas chromatography‐mass spectrometry (GC‐MS), using selected‐ion monitoring and internal standards. The method has been evaluated by nine flavour‐industry laboratories using a complex surrogate flavouring containing all of the above analytes, at concentrations that would be likely to produce levels in finished foods of around typical maximum limits for these RS. Results were obtained from a total of 15 columns and sets of analytical conditions, using 11 GC/MS instruments, with in each case a determination of the analyte in two versions of the flavouring. With reproducibility relative standard deviations (RSDR) of less than about 20%, and recoveries of 80–120%, the method performance can be considered as satisfactory for rapid routine checks on the levels of restricted substances in compound flavourings. The method is intended for flavour‐industry laboratories in order for them to fulfil their obligation to inform food‐industry clients of the amounts of these substances in commercial flavourings, but is not intended for their analysis in finished foods. Copyright © 2014 John Wiley & Sons, Ltd.